Uji Eksperimental Aliran Dalam Pipa dengan Variasi Rangkaian Pompa Sentrifugal - Amrullah; Akbar Naro Parawangsa; La Ode Ahmad Barata (Program Pendidikan Vokasi Teknik Mesin, 2024)
A pump converts the rotational energy of the shaft and subsequently the movement of the blades into kinetic energy and pressure in the fluid. Pumps can be configured as single, double series, or double parallel, depending on the requirements. This research aims to determine the best performance of a centrifugal pump installation with variations in head and configuration. The method used in this research is experimental, utilizing a centrifugal pump arranged with water as the fluid. The results show that single and double series configurations are more suitable for applications requiring stable flow despite changes in head. Parallel configurations produce higher speeds compared to single and double series configurations, but speed decreases with increasing head. The single pump's efficiency increases to 40.5% with an increase in head. Efficiency in the series configuration increases to 50.1%, higher than the single pump at the same head. Efficiency in the double parallel configuration increases to 80.1%, indicating that the parallel pump is the most efficient at higher heads. For applications requiring high efficiency, the double parallel pump configuration is the best choice. Based on the analysis results, it can be concluded that the double parallel pump configuration provides the best performance with the highest efficiency at 80.1%, and the highest discharge rate of 43.2 l/min. The double parallel pump configuration is the most efficient and effective for applications requiring optimal pump performance at higher heads.